Association Between Nutritional Status and Development of Preschool Children at An-Nizam Kindergarten, North Sumatra: A Cross-Sectional Study - Ardiana Batubara; Fitriyani Pulungan; Nur Afifah Harahap; Melani Puteri Asri Harahap (Gema Lingkungan Kesehatan, 2026)
This study aims to analyze the implementation of administrative innovations in the Healthy Indonesia Program with a Family Approach (PIS-PK) and its impact on program effectiveness and family participation. The research method used a qualitative approach with data collection through in-depth interviews, participant observation, and documentation of PIS-PK administration in four community health centers. Data analysis was conducted through data reduction, coding, comparisons between community health centers, and triangulation to ensure the validity of the findings. The results showed that administrative innovations included digitizing family data, standardizing health forms and indicators, digital data-based monitoring, family education and participation, and cross-stakeholder coordination. The implementation of these innovations increased the accuracy and efficiency of data collection, accelerated reporting, facilitated the identification of priority families, and encouraged active family involvement. The main challenges included limited human resources, infrastructure, and community adaptation to the digital system. However, strategies such as routine training, portable hotspots, and cadre mentoring were able to overcome these challenges. This study provides an important contribution to the development of standardized and integrated data-based family health service administration and environmental health management.